PENGARUH BUDAYA ORGANISASI TERHADAP PEGAWAI PADA PT. ANGKASA PURA II (PERSERO) SULTAN SYARIF KASIM PEKANBARU (Studi Kasus Pada Bagian Pertolongan Kecelakaan Pesawat dan Pemadam Kebakaran) - Gultom, Elida (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This research was conducted at PT. Angkasa Pura II (Persero) Sultan Syarif Kasim II International Airport - Pekanbaru. The purpose of this study was to determine the influence of organizational culture on employee performance at PT. Angkasa Pura II, Sultan Syarif Kasim II International Airport - Pekanbaru. The population in this study were all employees Section Airport Rescue and Fire Fighting (ARFF), which amounted to 34 people. In this study, the sampling using saturated sample, the population sampled by 33 people (researchers is one of the clerks in Section Airport Rescue and Fire Fighting (ARFF), thus excluding the sample). Analysis of data using simple linear regression. The results showed that organizational culture significantly influence employee performance in Section Airport Rescue and Fire Fighting (ARFF). The magnitude of the influence of organizational culture on employee performance amounted to 50.2% while the remaining 49.8% describe other independent variables that are not observed in this study. Recommendations can be submitted to the PT. Angkasa Pura II (Persero) Sultan Syarif Kasim II International Airport - Pekanbaru, to be more regard about organizational culture is applied, because the organizational culture has a great influence, ie 50.2%